Consumer Demand for Environmental, Social, and Ethical Information in Fishery and Aquaculture Product Labels - Peiró-Signes, Angel; Miret-Pastor, Lluís; Galati, Antonino; Segarra-Oña, Marival (Frontiers in Marine Science, 2022)
Customers’ attention to sustainability labels in fishery and aquaculture products (FAPs) has been increasing in the last decades, and the industry has adapted to this growing interest by adopting fish ecolabels. However, there is a growing interest to widen the sustainability concept to include the social and ethical information of the fishery and aquaculture industry and to go further from the voluntary approach on the labeling of these aspects in FAPs. For this reason, using data from 2021 Eurobarometer and using machine learning techniques, we disentangle the characteristics of the FAP buyers that consider the importance of environmental impact, ethical, and social information appearing on FAP labeling. The results confirmed that most of the consumers who consider environmental, social, and ethical aspects when buying FAPs also think that this information should be labeled. In line with other works, young, educated, and environmentally aware consumers in high-income countries are more likely to request this information in the FAP label. One interesting finding of the study relates with the asymmetric impact of the variables and the important group of respondents who do not consider these aspects but also advocate to include them in the FAP label. The study outcomes can be beneficial for policymakers to design future public policies regarding FAP labeling, as well as to be taken into consideration in the marketing policies of fishery and aquaculture producers and retailers.